Dampak Media Sosial Terhadap Kesehatan Mental Mahasiswa: Kajian Terhadap Korelasi Intensitas Penggunaan dan Tingkat Kecemasan - Mochammad Hatta Kimura Raya Ramkar; Naufal Azhar; Astika Ayu Pratiwi; Ferdian Dwi Saputra; Andri Sahata Sitanggang (Inovasi Kesehatan Global, 2025)
Intensive social media use has become an ingrained phenomenon in the daily lives of college students. Technological developments and high accessibility to digital platforms cause students to spend a significant amount of time interacting virtually. This condition has various psychological implications, one of which is increased anxiety levels. This study aims to determine the relationship between the intensity of social media use and anxiety levels in college students. The method used was a quantitative approach with a correlational design through a survey distributed to a number of student respondents from various study programs. The research instruments included a questionnaire regarding the frequency of social media use and a validated anxiety scale. The results showed a significant relationship between the intensity of social media use and students' anxiety levels. The higher the frequency of social media use, the greater the tendency for students to experience anxiety. Several factors that trigger anxiety include social comparison with other users, the need for validation through the number of "likes" and comments, and the pressure to project an ideal self-image online. Furthermore, most students expressed feelings of anxiety or restlessness when not accessing social media for a certain period of time, indicating psychological dependence. These findings indicate that social media has a significant influence on students' psychological conditions, particularly in triggering anxiety. Therefore, it is crucial for higher education institutions, educators, and parents to provide education on healthy and balanced social media use. Preventive and promotive interventions to support student mental health are essential to mitigate the negative impacts of social media and foster wiser digital behavior in today's technological era.